Pedagogical management and school performance in the area of mathematics - Bravo-Aranibar, Julio C. (2020)
The research aimed to demonstrate the incidence of pedagogical management in the school performance of the area of ​​mathematics in secondary school students of the educational institution Santo Domingo de Jicamarca-Lima 2018. The research is quantitative, with a type and descriptive correlational design. The data collection instrument that was used is the survey, validated by expert judgment and establishing the reliability of 0.91 on the Cronbach Alpha scale. We worked with a sample consisting of: 72 fourth-year students and 60 fifth-year students. The results show that there is a positive relationship of 0.862 between pedagogical management and school performance in the area of ​​mathematics in secondary school students; Therefore, it is concluded that it is important to make profound changes in the conception of educational environments and in the curricular field, including contents and pedagogical managements.